2020
DOI: 10.1109/tit.2020.2967753
|View full text |Cite
|
Sign up to set email alerts
|

An Index Coding Approach to Caching With Uncoded Cache Placement

Abstract: Caching is an efficient way to reduce network traffic congestion during peak hours, by storing some content at the user's local cache memory, even without knowledge of user's later demands. Maddah-Ali and Niesen proposed a two-phase (placement phase and delivery phase) coded caching strategy for broadcast channels with cache-aided users. This paper investigates the same model under the constraint that content is placed uncoded within the caches, that is, when bits of the files are simply copied within the cach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 44 publications
1
102
0
Order By: Relevance
“…Such a scheme is referred to as the MN scheme in this paper. In [21], using graph theory the authors showed that when K ≤ N the MN scheme has minimum transmission rate under uncoded placement. Hence the MN scheme has also been widely used in various networks [1], [6]- [8], [10]- [13].…”
Section: B Prior Workmentioning
confidence: 99%
“…Such a scheme is referred to as the MN scheme in this paper. In [21], using graph theory the authors showed that when K ≤ N the MN scheme has minimum transmission rate under uncoded placement. Hence the MN scheme has also been widely used in various networks [1], [6]- [8], [10]- [13].…”
Section: B Prior Workmentioning
confidence: 99%
“…Caching strategies can be categorized into uncoded techniques [98]- [100] and coded techniques [101]- [103] based on the stored content type. In the uncoded technique, the whole file or a fractional portion of the file is stored in the caching node.…”
Section: Caching Strategiesmentioning
confidence: 99%
“…The proof of Theorem 2 utilizes Lemma 2 in [9] which is based on the approaches in [3], [12] and provides a lower bound on the entropy of all transmissions in the Shuffle phase given a specific function and file placement and a permutation of the computing nodes.…”
Section: Appendix C Proof Of Theoremmentioning
confidence: 99%